Dissecting MHC class II export, B cell maturation, and DM stability defects in invariant chain mutant mice. - Koonce, C; Bikoff, E (2004)
Invariant (Ii) chain loss causes defective class II export, B cell maturation, and reduced DM stability. In this study, we compare Ii chain and class II mutant mouse phenotypes to dissect these disturbances. The present results demonstrate that ER retention of alphabeta complexes, and not beta-chain aggregates, disrupts B cell development. In contrast, we fail to detect class II aggregates in Ii chain mutant thymi. Ii chain loss in NOD mice leads to defective class II export and formation of alphabeta aggregates, but in this background, downstream signals are misregulated and mature B cells develop normally. Finally, Ii chain mutant strains all display reduced levels of DM, but mice expressing either p31 or p41 alone, and class II single chain mutants, are indistinguishable from wild type. We conclude that Ii chain contributions as a DM chaperone are independent of its role during class II export. This Ii chain/DM partnership favors class II peptide loading via conventional pathway(s).